2021
DOI: 10.3390/molecules26092438
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols and Fish Oils for Improving Metabolic Health: A Revision of the Recent Evidence for Their Combined Nutraceutical Effects

Abstract: Polyphenols and omega-3 polyunsaturated fatty acids from fish oils, i.e., eicosapentaenoic and docosahexaenoic acids, are well-recognized nutraceuticals, and their single antioxidant and anti-inflammatory properties have been demonstrated in several studies found in the literature. It has been reported that the combination of these nutraceuticals can lead to three-fold increases in glutathione peroxidase activity, two-fold increases in plasma antioxidant capacity, decreases of 50–100% in lipid peroxidation, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 111 publications
(110 reference statements)
0
18
0
Order By: Relevance
“…These findings led us to hypothesize that taurine could serve as a healthy additive in fish oil dietary supplements. Moreover, some polyphenols exhibit potent antioxidant and anti-inflammatory effects, allowing them to show synergistic, additive, or complementary effects with fish oil [ 71 , 72 , 73 ]. Further work is needed to determine how these nutraceuticals interact with each other in vivo and their primary mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…These findings led us to hypothesize that taurine could serve as a healthy additive in fish oil dietary supplements. Moreover, some polyphenols exhibit potent antioxidant and anti-inflammatory effects, allowing them to show synergistic, additive, or complementary effects with fish oil [ 71 , 72 , 73 ]. Further work is needed to determine how these nutraceuticals interact with each other in vivo and their primary mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, polyphenols are absorbed in the intestine after being hydrolyzed by intestine enzymes and the host's microbiota ( 126 ). Then, the resulting molecules can interact with free radicals and inhibit enzymes involved in the AA pathway, modulating the inflammatory response and blocking the AA pathway ( 14 ). Besides that, endothelial cells are also being stimulated by both products from polyphenols and ω-3 PUFAs metabolization to produce NO and H 2 S in the first case, which will aid the resolution of the inflammatory situation and the tissue regeneration, or trigger signaling cascades by interacting with cell membrane receptors such as vascular endothelial growth factor (VEGF) or blocking p-AKT, NF-κB, and MMP-9 activities ( 122 , 127 ).…”
Section: Polyphenols and ω-3 Pufas Mechanisms On Obesity And Its Rmdsmentioning
confidence: 99%
“…In addition, several studies have reported a decrease in obesity and its RMDs due to consumption of vegetables (leaves, seeds, nuts, fruits, vegetable oils, by-products) and fish (mainly marine fish, oils, byproducts) rich in polyphenols and ω-3 PUFAs: ALA, EPA, and DHA (7)(8)(9)(10)(11)(12)(13). Furthermore, obesity and its RMDs lowering can be explained by consequence of synergistic actions of polyphenols and ω-3 PUFAs improving several metabolic health pathways (14,15). Due to the synergistic actions of the polyphenols and ω-3 PUFAs, some products that are found, like fish and vegetables, and their by-products can potentially improve and control obesity and its RMDs as anti-glucose tolerance, anti-oxidative, anti-atherosclerosis, antiinflammation, anti-weight gain, hepato-protective, vascularprotective, cardiovascular-protective, anti-hypertension, antidiabetic effects, thus improving the human health (13,(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse methodological approaches are used to delve into the molecular mechanisms subjacent to polyphenol effects, including assays in specialized cell lines [ 16 , 17 ], microorganisms [ 18 ], model organisms such as the nematode C. elegans [ 19 ], or mice models [ 20 ], as well as molecular docking studies upon potential target proteins [ 20 ], involving distinct polyphenols, either as pure compounds [ 19 ] or diverse and complex phenolic mixtures [ 16 , 18 , 20 , 21 ]. In addition, interactions with non-phenolic bioactives, such as cannabinoids [ 17 , 22 ], humulones and lupulones [ 22 ], or polyunsaturated fatty acids [ 23 ] are explored.…”
mentioning
confidence: 99%
“…The published papers describe a range of activities for polyphenols, including antioxidant [ 19 , 23 ], anti-inflammatory [ 20 , 24 ], anticancer [ 21 ], neuropreventive [ 16 ], analgesic and antipyretic [ 20 ], estrogenic [ 22 ], and antiviral [ 18 ]. Further, the therapeutic potential of this family of compounds for the prevention or treatment of distinct human diseases, beyond their recognized cardiovascular protective effect, is shown, such as for bowel disorders [ 25 ], breast cancer [ 21 ], prostatic hyperplasia [ 24 ], and ocular degenerative diseases [ 26 ].…”
mentioning
confidence: 99%